ASSESSING THE IMPACT OF BRAND IDENTITY ON BRAND PERFORMANCE, BRAND SATISFACTION AND BRAND LOVE IN IRAN - Souri, Farbod (The journal of contemporary issues in business and government, 2021)
In recent years, the issue of brand identity has become more and more important to academics and researchers. It stands to the reason that managers and market analysts have become aware of the value of the brand. Since many people make decisions based on the brand name, logo and color, brand identity is an important component in helping a business thrive and is the goal, mission, vision, feeling and voice of the company. In fact, it can be said that brand identity is a mixture of science and art. Therefore, considering the importance of brand identity, this study seeks to evaluate the impact of brand identity on brand performance, brand satisfaction and brand love in Iran. The statistical population of this study consists of employees of a government organization in Tehran, whose number in 1399 was 513 people. By using simple random sampling method, 265 questionnaires were distributed and among these, 205 correct questionnaires were selected for analysis. The data collected from the questionnaire are measured by confirmatory factor analysis (CFA) technique and AMOS software. Findings from the analysis of research results showed that brand identity has affected brand performance. Also, a significant relationship was found between brand identity and brand satisfaction. Other evidence points to the impact of brand identity on brand love.